The Sharpin interactome reveals a role for Sharpin in lamellipodium formation via the Arp2/3 complex - Meraj H. Khan; Siiri I. Salomaa; Guillaume Jacquemet; Umar Butt; Mitro Miihkinen; Takahiro Deguchi; Elena Kremneva; Pekka Lappalainen; Martin J. Humphries; Jeroen Pouwels (The Company of Biologists Ltd, 2022)
Sharpin, a multifunctional adaptor protein, regulates several signalling pathways. For example, Sharpin enhances signal-induced NF-κB signalling as part of the linear ubiquitin assembly complex (LUBAC) and inhibits integrins, the T cell receptor, caspase1 and PTEN. However, despite recent insights into Sharpin and LUBAC function, a systematic approach to identify signalling pathways regulated by Sharpin has not been reported. Here, we present the first ‘Sharpin interactome’, which identifies a large amount of novel potential Sharpin interactors in addition to several known ones. These data suggest that Sharpin and LUBAC might regulate a larger number of biological processes than previously identified, such as endosomal trafficking, RNA processing, metabolism and cytoskeleton regulation. Importantly, using the Sharpin interactome we have identified a novel role for Sharpin in lamellipodium formation. We demonstrate that Sharpin interacts with Arp2/3, a protein complex that catalyses actin filament branching. We identified the Arp2/3-binding site in Sharpin and demonstrate using a specific Arp2/3-binding deficient mutant that the Sharpin-Arp2/3 interaction promotes lamellipodium formation in a LUBAC-independent fashion.